PENGARUH PROGRESSIVE PART METHOD TERHADAP KEMAMPUAN LEMPAR CAKRAM PESERTA DIDIK MA KHULAFAUR RASYIDIN - Richman, Rohendri; Triansyah, Andika; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is whether there is an effect of the progressive part method on the ability of the MA student Khulafaur Rasyidin's discus throwing. This study aims to determine the effect of the progressive part method on the ability of throwing discs for MA Khulafaur Rasyidin students. The method used is an experimental method in the form of research True-Experimental Pretest-Posttest Control Group Design. The population in this study were 27 students at MA Khulafaur Rasyidin. The sample used was 25 people. Data analysis with parametric test and t-test. From the results of the research carried out, it is known that there is a significant influence on the progressive part method on the ability of MA Khulafaur Rasyidin's student discus throwing. The results of the t-test analysis showed that the t-count was 15.89> t-table 2.064. The magnitude of the percentage of the effect of the progressive part method given on the ability of MA Khulafaur Rasyidin's student discus throwing was 73.80%.Â Keywords: Progressive Part Method, Lempar CakramÂ